Image-Guided Percutaneous Ablation of Hepatic Malignancies - Foltz, Gretchen (Seminars in Interventional Radiology, 2014)
The liver is a common site of primary and secondary malignancies, often resulting in significant morbidity and mortality. Evaluating these patients in a multidisciplinary setting allows for optimal utilization of all oncologic therapies including surgery, radiation, systemic chemotherapy, transarterial therapies, and ablation. While surgical intervention often provides the best outcomes when treating most hepatic tumors, many patients are not surgical candidates due to extensive tumor burden, underlying liver disease, or other comorbid conditions. The evolution of imaging and ablation devices has allowed for the increased utilization of percutaneous ablation as definitive and palliative treatment of primary and metastatic hepatic malignancies. Ablation induces tumor necrosis by injection of chemicals (chemical ablation) or temperature modification (thermal ablation). The goal of this review is to provide an overview of different ablation techniques commonly used for hepatic malignancies, discuss the oncologic outcomes of these interventions, and outline the current indications, contraindications, and reported complications of these therapies.
Keywords: percutaneous ablation; hepatocellular carcinoma; hepatic metastases; interventional radiology